Sing Sing Sing : Poems. - Murphy, Bruce (NYU Press, 1990)
Sing, Sing, Sing is unlike any recent first collection by an American poet. It goes against the grain of contemporary fashion by replacing prosaic narrative with a lyricism both symbolic and mysterious. This poet can appreciate experience as "the open/End of a bag fill/With ordinary things," yet also he has an ear for "a watch that goes on ticking/Underground," the shadow of history that lies across the present. Murphy manifests a sense of responsibility for protecting the spirit of lost people and lost things. But in their concern for posterity, his poems use language to f.